Manyang Dut training in the backyard of local boxer and trainer Daniel Ford, Toronto, Lake Macquarie, New South Wales, 2014 - Ashleigh, Conor, 1987- (2014)
"Manyang Dut skips during a training session inside the backyard of local boxer and trainer Daniel Ford, in Toronto a lakeside suburb within the city of Lake Macquarie, between Newcastle and Sydney. Manyang, 19 years old, has won a number of national and state amateur boxing belts in recent years and his trainers Shane Wells, left and Ford think he may be ready to have a shot at professional boxing. Manyang arrived in Australia at 11 years of age in 2005 with his Mother two brothers and three sisters."--Information supplied by photographer.
Title from acquisitions documentation.
Part of the collection: Australia's South Sudanese refugee community, 2010-2015.
Keywords: Dut, Manyang -- Photographs; Boxers (Sports) -- New South Wales -- Toronto -- Photographs; Sudanese Australians -- New South Wales -- Toronto -- Photographs; Garages -- New South Wales -- Toronto -- Photographs; Refugees -- Sudan -- Photographs; Toronto (N.S.W.) -- Buildings, structures, etc. -- Photographs; Lake Macquarie (N.S.W.) -- Photographs; Refugees